Development of supercapacitors with in-situ polymerized polyaniline on MnO2 and Co3O4 anodes and activated carbon cathodes - Izan Izwan, Misnon (2016)
Supercapacitors (SCs) store electrochemical energy at an electrode – electrolyte interface with high power density (PD), fast recharge capability and long cycle life. The SCs are two types according to the charge storage mechanisms: electric double layer capacitors (EDLCs) and pseudocapacitors (PCs). Allotropes and polymorphs of carbon are choice to build EDLCs electrodes whereas PCs are built from nanostructured metal oxides, hydroxides, chalcogenides and conducting polymers. Broad objective of this doctoral research is to develop a SC device with PC as anode and EDLC as cathode – this type of devices are called asymmetric supercapacitors (ASCs). Popular PC electrodes such as MnO2 and Co3O4 have poor electrical conductivity – making their composite with conducting polymers such as polyaniline (PANI) is proposed to be a superior PC electrode. In this research, MnO2 and Co3O4 were synthesized by hydrothermal reaction and molten salt methods and their polymeric composite were developed by in situ polymerization. The materials were characterized by thermal analyses, X-ray and electron diffraction, FTIR spectroscopy, gas adsorption studies, scanning and transmission electron microscopy, and cyclic voltammetry. The electrochemical properties of the electrodes were evaluated systematically using cyclic voltammetry, galvanostatic charge–discharge cycling, and electrochemical impedance spectroscopy. The relationship between the pores in the electrodes and the size of the solvated ions in the electrolyte on the final capacitance in various aqueous electrolytes were investigated – the pores smaller than the size of the solvated ions do not contribute to the capacitance of the electrode. Aqueous KOH shown the best diffusion coefficient (6.8 × 10-10 cm2 s-1) and capacitive properties in this study; therefore, it was chosen as the electrolyte of choice. The PANI provided faster ion channeling to the surface of metal oxides and showed improved charge storage capacity than their bare analogues. Highest specific capacitance (CS) obtained in this study was in a PANI composite of Co3O4 synthesized by the molten salt method (CS ~985 F g-1 at 2 mV s-1), recording an increase of ~253% compared to its bare analogue. Three choice of EDLC electrodes were considered in this study, viz. (i) activated carbon from palm kernel shells (PKS) as it form a local abundant natural resource, (ii) commercial activated carbon (AC), and (iii) ordered mesoporous carbon (OMC). The PKS were pyrolyzed and activated using physical and chemical activation methods whereas the other two were obtained from commercial sources. Structural, thermal, morphological, surface, and electrochemical properties of the carbon electrodes were also systematically studied as done for the PC electrodes. The PKS activated carbon showed high areal capacitance (~45 F cm-2), which is one of the highest reported so far in literature, besides showing high cycle stability (95–97%). The ASCs were fabricated using the PC electrodes as anodes and carbons as cathodes. For MnO2 series, PANI-MnO2 (hydrothermal)//OMC recorded the highest energy density (ED) ~27 Wh kg-1 at PD ~400 W kg-1 whereas for Co3O4 series, PANI-Co3O4 (hydrothermal)//OMC gives ED of ~23 Wh kg-1 at similar PD. Despite its nominally smaller ED, the Co3O4 based device showed superior cycling stability than the other.